Temperature and Humidity measurement of Baby Incubator using PSOC CY8CKIT-062-WiFi-BT - Navanath N Kumbhar; Shivprasad K. Tileka; Prashant V. Mane-Deshmukh (Universitas Komputer Indonesia, 2025)
The present work deals with the development of a temperature and humidity monitoring system designed specifically for neonatal intensive care units (NICUs), which serve as dedicated spaces for premature or fragile newborns. These units aim to replicate the conditions of a mother's womb, essential for the survival and growth of vulnerable infants. Maintaining proper thermoregulation is critical, as failure to do so remains a significant, yet preventable, cause of mortality among neonates. For premature and delicate infants, consistent body temperature is vital for optimal development. This project focuses on monitoring and regulating the temperature and humidity levels within the NICU, as these factors play a key role in the well-being of preterm infants. The system utilizes a set of specialized sensors, with the collected analog signals processed through a Programmable System-on-Chip (PSoC 6) microcontroller architecture to ensure high-precision and efficient monitoring.